The creative arts in palliative care - Hartley, Nigel; Payne, Malcolm, 1947- (Jessica Kingsley, 2008)
Use of the arts in palliative care settings is a powerful and effective way of addressing the practical, psychological, social and spiritual issues faced by service users in end-of-life care. The Creative Arts in Palliative Care uncovers the possibilities for using the creative arts and provides guidance on how to implement arts projects successfully. Part 1 focuses on designing objectives for the creative arts in palliative care - such as self-fulfilment, social participation, diversion from pa.